Linking management practices to innovation capabilities - Bittar, Alexandre de Vicente (2019)
The literature provides a diversity of concepts about the innovation capability. There is a variety of definitions, a lack of consensus on their structuring and a dispersion of specialized terms of innovation capabilities, along mainly with the disconnection between capabilities perspective and Operations Management and Innovation literatures. It is perceived that for several times these literatures use the term capability but distance itself from the capabilities theory, which should be its base. It is usual to have no mention or debate about resources, routines, practices, skills, knowledge, experience and characteristics of the company, which are the building blocks of a capability. At the same time, there is a detachment from the business management: the discussion deepens into the theoretical field, moving away from business applicability. There is one building block introduced recently in the Operations Management literature which has the capacity to approach theory and business management: a practice-based approach. Innovation capability can be conceptualized and measured as a bundle of practices. The set of practices leading to innovation capability and improvement capability is underdeveloped in the literature, and there is an opportunity to deepen this field of research and to identify their impact on the performance. Conducting a mixed method research, the main objective of this research is to understand the impact of improvement and innovation capabilities as a bundle of practices on operational and innovation performance of manufacturing plants. The research is divided in three phases. In the first phase, there is a systematic literature review of the current literature on innovation capability, aiming to understand the capabilities for innovation management and their factors and determinants in organizations. The main contribution is the proposition of frameworks mapping antecedents and consequences of improvement and innovation capabilities. The second phase focus on a quantitative methodology based on confirmatory factor analysis (CFA) and structural equation modelling (SEM) using lavaan package of the R software. The sample was extracted from the HPM database: 275 manufacturing plants located in 15 countries and 3 industries. First, it was modeled the improvement capability as a second order construct, formed by TQM practices (top management leadership for quality and supplier quality involvement) and HR practices related with TQM (small group problem solving). Then, it was modeled the innovation capability as a second order construct, formed by Open Innovation practices (customer involvement in NPD and supplier Involvement in NPD), Knowledge Management practices (knowledge absorption from customers), and Anticipation of New Technologies practice. It was found that: improvement and innovation capabilities have a high correlation; improvement capability as a bundle of practices has a positive and significant impact on operational performance; and innovation capability as a bundle of practices has a positive and significant impact on product innovation performance. However, there was no significant relation between innovation capability and process innovation performance. The main contribution of this phase is to enlarge the practice-based approach of innovation capabilities, confirming a positive impact on performance. Phase 3 is a qualitative study in the manufacturing sector. It was conducted a multiple case study in order to explore the management practices used in 6 world class industries related with improvement and innovation capabilities and that contributes with performance, and to compare these practices with theory and with the model tested in phase 2. It was developed a protocol and a semi-structure questionnaire used to interview 23 executives of these companies. The interviews were recorded, transcribed and analyzed using a qualitative data analysis software (Atlas.ti). Secondary data were obtained from companies reports and content published in newspapers, magazines, internet sites and notes taken during the factories’ visits, enabling triangulation. The main contribution is the proposition of a framework of improvement capability based on 13 practices and of innovation capability based on 16 practices.